Birth order and parental nurturance from the perspective of emerging adults - Tan,Erris Maristelle Pauline Enano; Cabuco, Michelle Carla (College of Home Economics, University of the Philippines Diliman, 2020)
Nurturance given by parents to their children changes as more are born into the family, which implies that birth order may be a factor in the differences of nurturance received by each child in the family. Children in emerging adulthood are especially able to assess the nurturance they receive, as they are of a mature and almost independent age. This exploratory and qualitative study aims to identify the characteristics of the different birth orders, namely the eldest child, middle child and youngest child. It seeks to describe the nurturance they perceive to obtain from their parents, and explore the relationship, if any, between parental nurturance and birth order in the context of emerging adults enrolled in UP Diliman. In-depth interviews of 24 purposely sampled emerging adults will be done to collect data, eight from each birth order. Findings will be analyzed through thematic analysis and results will be compared and contrasted between birth orders. Relevant theories will also be applied to explain common phenomena.